Sex for sale in Scotland : prostitution in Edinburgh and Glasgow, 1900-1939 - Settle, Louise (Edinburgh : Edinburgh University Press, 2016)
Sex for Sale in Scotland examines the various methods that were used to police female prostitution in Edinburgh and Glasgow between 1900 and 1939, with particular emphasis on the experiences of the women involved.
Controlling the 'social evil' : policing prostitution -- The social geography of prostitution -- Reforming the 'fallen' : voluntary organisations, probation and the informal regulation of prostitution -- Women's experiences of prostitution -- Dance clubs and ice-cream tubs : clandestine prostitution and the Kosmo Club.
Title from publisher's bibliographic system (viewed on 29 Sep 2017).
Keywords: Prostitution -- Scotland -- History -- 20th century